Impelementasi Kebijakan Pemerintah dalam Mengoptimalkan Kinerja Pegawai Negeri Sipil untuk Meningkatkan Kualitas Pelayanan Jaminan Kesehatan Nasional-Badan Penyelenggara Jaminan Sosial Kesehatan - Aloi Kamarasyid (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2017)
The program of government is ruled by an organization which is pointed out to perform as the first target. But there are not programs of government has not been maximumly ruled by the organization which is pointed. The program of guarantee of national health of the board of social guarantee at The Common Hospital of South Bangka Hospital, Regional Hospital of Pangkalpinang, Bhakti Timah Hospital Pangkalpinang hasn’t succeeded maximum. It is caused by the medical workers haven’t been suitable, the sum of doctors are not enough, the facilities haven’t been enough, a few of socialisations about the programs. It is needed the policy of the government to manage the programs so the service of heath can be touched for all people of South Bangka, Pangkalpinang according to the law of Republic of Indonesia number 24 in the year 2011, the regulation of minister of the heath of Republic of Indonesia number 28 in the year 2014. The policy of government is influenced by four of communication factors, human resource, disposition, and bureaucratic structure, whereas the work of civil government officers to give a service of guarantee of national health, the board of social guarantee at The Common Hospital of South Bangka, The Regional Hospital of Pangkalping, and The Bhakti Timah Hospital hasn’t been ability, motivation, and maximum chance. The utility of the writing to see the work of civil government officers in giving a service of national guarantee, the board of social guarantee.